Prepectoral Breast Reconstruction with Fenestrated Acellular Dermal Matrix: A Novel Design. Issue 4 (April 2018) - Paydar, Keyianoosh Z.; Wirth, Garrett A.; Mowlds, Donald S.
Abstract : Summary: Fenestrated acellular dermal matrix (ADM) has improved patient outcomes in both direct-to-implant and 2-stage tissue expander/implant breast reconstruction. This technical alteration utilizes optimal fenestration overlap to enhance the breast reconstruction experience. We present a novel, surgeon-designed shaped fenestrated ADM, placed in the recently repopularized prepectoral pocket for anterior coverage of implants in direct-to-implant and 2-stage breast reconstruction. A retrospective review of 10 patients (18 breasts) who underwent direct-to-implant or 2-stage breast reconstruction utilizing fenestrated shaped ADM in the prepectoral plane at a major academic institution in 2016 was conducted. Sixteen breasts (88.9%) underwent direct-to-implant reconstruction, and 2 breasts (11.1%) received tissue expanders. All reconstructions were performed using FlexHD Pliable ADM with surgeon-designed shape and fenestrations. The average implant size was 544.4 cc (±137.2 cc). The average intraoperative tissue expander fill volume measured 450 cc (90% of tissue expander size). The single expander case utilized 1 office fill (day 21) for full expansion. Major complications requiring reoperation within 90 days postoperatively were observed in 22.2% (4 breasts) of reconstructions. Three breasts (16.7%) due to partial mastectomy flap necrosis, 1 breast (5.5%) explantation due to infection. There was no seroma or capsular contracture. Prepectoral reconstruction with shaped fenestrated ADM is safe with high intraoperative fill volumes and facilitates more direct-to-implant reconstructions. Patients undergo fewer postoperative expansions, experience less time to full expansion, and subjectively report less pain. Patients benefit from improved cosmetic outcomes with better shape and no functional loss or animation deformity. Abstract : Supplemental Digital Content is available in the text.